WITTGENSTEIN IN TOLSTOJ O ETIKI IN O SMISLU ŽIVLJENJA (Filološke pripombe, 2019)
Some key similarities between Wittgenstein’s ethical-logical standpoint in the time of Tractatus and the philosophical-spiritual standpoint of the late Tolstoy are described. The thought on the non-speakable meaning of life by both thinkers and the wish for a “non-problematic” life by both thinkers is exposed. For both the problem of the meaning of life is dissolved in the disappearance of this problem, if we can see at our life “sub specie aeterni”, i. e. from the atemporal newness.
Keywords: Wittgenstein, Tolstoy, meaning of life, non-speakable, world as wholeness, moral claim